Single Jejunum Metastasis from Breast Cancer Arising Twelve Years after the Initial Treatment - Cláudia Paiva; José Garcia; Cristina Silva; Alexandra Araújo; António Araújo; Marisa D. Santos (Case Reports in Oncological Medicine)
Metastatic involvement of gastrointestinal tract from breast cancer is a rare event. We report the case of a 61-year-old woman presenting with bowel obstruction, related to metastasis of a primary breast cancer she had 12 years earlier (a triple-negative invasive ductal carcinoma treated with surgery and chemotherapy). Bowel obstruction was caused by a 20-centimeter tumor in the jejunum, involving also the transverse colon. The patient underwent en bloc resection of tumor with jejunum and transverse bowel segment and received adjuvant chemotherapy with carboplatin and paclitaxel. Twenty months later, she was alive without disease recurrence.